A Novel Monocyte-based Pyrogen Test Based on the Mechanism of Human Fever Reaction - Wang, Can; Dong, Shanshan; Zhao, Hongbo; Wang, Ziqiang; Zhou, Qin; Wu, Lihong; Shao, Hong; Chen, Gang (Current Pharmaceutical Analysis, 2016)
Background: Given that pharmacopoeia pyrogen tests, rabbit pyrogen test, and limulus amoebocyte lysate (LAL) test have some shortcomings, supplements for pyrogen tests are necessary. Objective: This study aimed to develop a novel monocyte-based pyrogen test. Method: The human promyelocytic leukemia cell line (HL-60), which was selected for its high sensitivity to pyrogens, such as lipopolysaccharide (LPS), zymosan, and lipoteichoic acid (LTA), was evaluated for interleukin- 6 (IL-6) production with IL-6 ELISA kit. The important parameters of the assay were researched, and a novel pyrogen test was developed. The linearity, reproducibility, and accuracy of the assay were verified, and the assay was compared with the LAL test by assessing the response to samples containing pyrogen. Results: HL-60/IL-6 assay was developed as a novel monocyte-based pyrogen test. The linearity between the pyrogen concentration and IL-6 amount was good (R2 > 0.96), and the RSD of the assay was not more than 20%. The recovery of pyrogens in biological products, such as monoclonal antibody, vaccine, and blood products, ranged from 50% to 200%. The pyrogen level detected by the assay was similar to that detected by LAL. Conclusion: The developed HL-60/IL-6 assay was a good supplement to traditional pyrogen tests for the detection of pyrogens, such as LPS, zymosan, and LTA.
Keywords: pyrogen test